2017
DOI: 10.1007/s00348-017-2319-9
|View full text |Cite
|
Sign up to set email alerts
|

Mixing layer development in compound channel flows with submerged and emergent rigid vegetation over the floodplains

Abstract: To cite this version:V. Dupuis, S. Proust, C. Berni, A. Paquier. Mixing layer development in compound channel flows with submerged and emergent rigid vegetation over the floodplains. Experiments in Fluids, Springer Verlag (Germany), 2017, 58 (4), pp.30. <10.1007/s00348-017-2319-9>. Author-produced version of the article published in Experiments in Fluids, 2017 The original publication is available at http://link.springer.com/article/10.1007/s00348-017-2319-9 DOI: 10.1007/s00348-017-2319-9Mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…Lateral profiles of mean velocities and turbulence quantities have been measured at different x-stations for each transition. As shown in our previous study (Dupuis et al, 2017), the properties of the compound channel mixing layer (width, dimensionless velocity difference λ, etc.) change across the water column.…”
Section: Mixing Layer Dynamicsmentioning
confidence: 60%
See 4 more Smart Citations
“…Lateral profiles of mean velocities and turbulence quantities have been measured at different x-stations for each transition. As shown in our previous study (Dupuis et al, 2017), the properties of the compound channel mixing layer (width, dimensionless velocity difference λ, etc.) change across the water column.…”
Section: Mixing Layer Dynamicsmentioning
confidence: 60%
“…In our previous study (Dupuis et al, 2017), we observed that for the two flows with uniform roughness CM and CW, the normalised profiles of longitudinal velocity and turbulence quantities were self-similar when going downstream. The velocity was normalised in the form (U − U 2 )/(U 1 − U 2 ) and, to take into account the mixing layer asymmetry, the lateral coordinate was normalised by the subsection mixing layer width, i.e.…”
Section: Normalised Lateral Profilesmentioning
confidence: 76%
See 3 more Smart Citations